Impact assessment of breast glandularity on relative biological effectiveness of low energy IORT X-rays through Monte Carlo simulation. (September 2021) - Shamsabadi, Reza; Baghani, Hamid Reza
Highlights: Influence of breast granularity on RBE of low energy IORT X-rays was assessed Different breast glandular fractions ranging from 0% to 100% glandular were considered Breast glandular fraction can affect both RBESSB and RBEDSB values Variations of RBEDSB was more obvious than RBESSB with changing the glandular fraction Abstract: Introduction: Intraoperative radiotherapy (IORT) by low energy X-rays is a single fraction treatment modality for tumor bed irradiation after breast-conserving surgery. It has been shown that the variations of breast tissue composition can affect the absorbed dose in this method. Apart from physical quantities such as absorbed dose value, radiobiological quantities including relative biological effectiveness (RBE) may also change with the variations of breast tissue composition. Accordingly, the current study aims to quantify both single and double-strand break RBE values (RBESSB and RBEDSB ) of low energy X-rays at different breast glandular fractions using a hybrid Monte Carlo (MC) simulation approach. Materials and methods: Produced low-energy X-rays by a validated MC model of INTRABEAM machine with 50 kV nominal voltage were considered as the radiation source. The secondary electron energy spectra at various depths inside the breast tissue with different glandular fractions were scored through GEANT4 MC Toolkit. Calculated spectra were then imported to MCDS MC code for DNA strand break calculation and RBE assessment. Both RBESSB and RBEDSB were calculated for various breast glandular fractions. Results: Changing the breast glandularity can affect both the trend of secondary electron spectra and relevant RBE values at different depths inside the breast volume. In this regard, RBESSB increments by about 1% with increasing the breast glandular fraction from 0% to 100%. On the other hand, RBEDSB decrements by about 3.3% with increasing the glandular fraction in the range of 0% to 100%. Variations of the depth within the breast tissue can also influence the RBE value so that RBESSB reduces by about 1% with increasing the depth from 2 mm to 10 mm one, while RBEDSB increases about 3.4%. The relevant RBESSB and RBEDSB values to the entire target volume (breast PTV) respectively increment and decrement by about 0.8% and 3.2% with increasing the breast glandularity from 0% to 100%. Conclusion: From the results, it can be concluded that the breast tissue composition has a measurable effect on RBE values of employed low energy X-rays during breast IORT which can cause variations of prescribed dose for patients with distinct breast glandularity fractions.